Kritik Sosial dalam Cerpen Manuel Karya Seno Gumira Ajidarma Tinjauan Sosiologi Sastra - Perdana, Adhi Dian; Alfiana, Nila; Ramadhani, Nur Fadhilah Rizqi; Yuliani, Nur Indah; Putri, Widya Ryolita (Kajian Bahasa dan Sastra (KABASTRA), 2023)
Orde Baru was the reign of President Soeharto which brought about a change in order over people's lives. In the 16th century East Timor was colonized by the Portuguese, then in 1975, East Timor proclaimed its independence and Indonesia made this territory of East Timor as the 27th province. Over time, conflicts arose between the Indonesian government and the people of East Timor who wanted independence. In the conflict, Indonesia became the object of conflict while the people of East Timor were made the subject of conflict. The conflict made the writer Seno Gumira Ajidarma moved to write works that represented the social life of his people. The work raised several issues of the Orde Baru government was the anthology book Saksi Mata which contained 13 short stories. In the anthology, there is a short story "Manuel" which will be used as the object of this research. The short story "Manuel" contains the author's criticism of the condition of East Timor during the New Order period. This study aims to show the social criticism in the short story and its usefulness in seeing the applicability of the criticism in times when conflicts occur with the present. The approach used in this study is a literary sociology approach. The technique used in this study is a literature review. From the results of the analysis, there are several social criticisms found in Manuel's short stories, among others, social criticism related to violence, social criticism related to human rights violations, social criticism of educational problems, and social criticism of health problems.